Scrutinizing Indonesian Students’ Understanding and Perceptions toward Plagiarism - Lisa Ramadhani Harianti; Ilham Mulya Putra Pradana; Betty Masruroh; Laksono Budiarto; Ravinesh Rohit Prasad (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Abstract: This study aims at investigating Indonesian students’ understanding of plagiarism practice during their final writing project (thesis and dissertation). Further, it also seeks to know the connection between their understanding and their responses to some situations that required them to discriminate against cases of plagiarism. We used a questionnaire provided by Turnitin. It was distributed to 131 undergraduate, graduate, and doctoral students from various universities in Malang, Indonesia. The questionnaire was disseminated through Google Forms in the first week of April 2021. The obtained data were analyzed using descriptive analysis. Our data analysis results showed that many of our participants present a great understanding of plagiarism. However, only less than the total participants have adequate skills in citing the work of other people. Also, interestingly, even in the lowest number, some of our participants have never heard of plagiarism checkers.